Inflammatory Bowel Disease, the Oral Contraceptive Pill and Pregnancy - Robert N Allan (Canadian Journal of Gastroenterology)
This paper summarizes our current knowledge of the role of the oral contraceptive pill in the pathogenesis of inflammatory bowel disease (IBO), followed by a review of fertility in women and men. IBD and pregnancy, including the impact on the fetus and the mother with ulcerative colitis or Crohn’s disease, is considered. The safety of drug treatment during pregnancy, the outcome of surgical treatment during pregnancy and the problems that may be encountered during pregnancy in patients with an ileostomy or ileo-anal pouch are discussed, followed by a review of the short and long term prognosis of ulcerative colitis and Crohn’s disease partition.